(untitled) (Mediscope, 2018)
Iodine is a micronutrient, which is essential for the synthesis of thyroid hormones. Thyroid hormones play a major role in the development of different functional components in different stages of life. The relationship between iodine intake level of a population and occurrences of thyroid disorders U-shaped with an increase from both low and high iodine intake. Iodine deficiency disorders (IDDs) are a major health problem worldwide in all age groups, but infants, school children, and pregnant and lactating women are vulnerable. During pregnancy and lactation, the fetus and infants are sensitive to maternal iodine intake. Even mild iodine deficiency may lead to irreversible brain damage during this period. A main cause of IDDs of neonates and infants is maternal iodine deficiency. Universal salt iodization strategy has been initiated by the World Health Organization and United Nation International Children Emergency Fund by the year 1993 for correction and prevention of iodine deficiency. Excessive iodine causes hypothyroidism, iodine-induced hyperthyroidism and autoimmune thyroid diseases. Iodine deficiency and excessive iodine, both cause goiter. There are many indicators for assessing the IDDs, such as measurement of thyroid size by palpation or ultrasonography, serum thyroid stimulating hormone, and thyroglobulin but these are less sensitive, costly and sometimes interpretation is difficult. Urinary iodine concentration (UIC) is a well-accepted, cost-efficient, and easily obtainable indicator of iodine status. Since the majority of iodine absorbed by the body is excreted in the urine, it is considered a sensitive marker of current iodine intake and can reflect recent changes in iodine status. Iodine requirements are greatly increased during pregnancy and lactation, owing to metabolic changes. During intrauterine life, maternal iodine is the only source of iodine for a fetus. UIC determines the iodine status of pregnant and lactating women. Breast milk is the only source of iodine for exclusively breastfed neonates and infants. Breast milk iodine concentration can be determined by UIC. UIC predicts the adverse health consequences of excessive iodine intake such as goiter, hypothyroidism, and hyperthyroidism. This review presents that iodine status in different groups of a population can be determined by UIC which will be helpful in assessing the iodine status in a community, finding out the cause of thyroid disorders, to predict the risk of adverse health effects of iodine deficiency and excessive iodine, and in making plan for iodine supplementation. Mediscope Vol. 5, No. 2: Jul 2018, Page 30-35